2018
DOI: 10.1038/s41438-018-0052-z
|View full text |Cite
|
Sign up to set email alerts
|

An AGAMOUS-like factor is associated with the origin of two domesticated varieties in Cymbidium sinense (Orchidaceae)

Abstract: Cymbidium has been artificially domesticated for centuries in Asia, which produced numerous cultivated varieties. Flowers with stamenoid tepals or those with multiple tepals have been found in different species of Cymbidium; however, the molecular basis controlling the formation of these phenotypes is still largely unknown. Previous work demonstrated that AGAMOUS/AG lineage MADS genes function in floral meristem determinacy as well as in reproductive organs development in both dicots and monocots, indicating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
4
10
0
Order By: Relevance
“…Remarkably, in Arabidopsis, ectopic expressions of TeAG1 and TeAGL11–1 resulted in short siliques, low seed setting rate, and sepal retainment at the bottom of mature siliques. This result was consistent with the finding reported in Cymbidium [ 49 ]. The expression analysis of endogenous gene STK suggested that short siliques with low seed setting rate might be correlated with the increased STK expression level in 35S:TeAG1 lines, while the short siliques with low seed setting rate might be associated with the decreased STK transcript level in TeAGL11–1 transgenic lines.…”
Section: Discussionsupporting
confidence: 94%
“…Remarkably, in Arabidopsis, ectopic expressions of TeAG1 and TeAGL11–1 resulted in short siliques, low seed setting rate, and sepal retainment at the bottom of mature siliques. This result was consistent with the finding reported in Cymbidium [ 49 ]. The expression analysis of endogenous gene STK suggested that short siliques with low seed setting rate might be correlated with the increased STK expression level in 35S:TeAG1 lines, while the short siliques with low seed setting rate might be associated with the decreased STK transcript level in TeAGL11–1 transgenic lines.…”
Section: Discussionsupporting
confidence: 94%
“…Remarkably, ectopic expression of TeAG1 and TeAGL11-1 resulted in short siliques with low seed setting rate and persistence of sepals at the bottom of mature siliques in Arabidopsis. This is consistent with the data reported in C. sinense [43]. The expression analysis of endogenous gene STK in 35S:TeAG1 lines suggested that short siliques with low seed setting rate correlated with increase of STK expression level, while the short siliques with low seed setting rate may associate with the decrease of STK transcripts in TeAGL11-1 transgenic lines.…”
Section: Discussionsupporting
confidence: 91%
“…Remarkably, in Arabidopsis, ectopic expressions of TeAG1 and TeAGL11-1 resulted in short siliques, low seed setting rate, and sepal retainment at the bottom of mature siliques. This result was consistent with the nding reported in Cymbidium [49]. The expression analysis of endogenous gene STK suggested that short siliques with low seed setting rate might be correlated with the increased STK expression level in 35S:TeAG1 lines, while the short siliques with low seed setting rate might be associated with the decreased STK transcript level in TeAGL11-1 transgenic lines.…”
Section: Functional Conservation and Diversity Of Teag1 And Teagl11-1supporting
confidence: 92%